2021
DOI: 10.3390/ani11030801
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium spp. and Giardia spp. in Free-Ranging Introduced Monk Parakeets from Santiago, Chile

Abstract: Monk Parakeets (Myiopsitta monachus) are medium-sized parrots that due to international pet trade currently exist as invasive species in 19 countries globally. Such is the case of Chile, where Monk Parakeets have thrived in the city of Santiago. Cryptosporidium spp. and Giardia spp. are worldwide distributed gastrointestinal parasites whose potential hosts include birds and humans. The present study sought to determine the presence of these pathogens in Monk Parakeets from Santiago. During the austral summers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…This finding confirms the presence of a zoonotic parasite in an abundant invasive synanthropic bird widely distributed in Santiago (Briceño et al, 2022;Sandoval-Rodríguez et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This finding confirms the presence of a zoonotic parasite in an abundant invasive synanthropic bird widely distributed in Santiago (Briceño et al, 2022;Sandoval-Rodríguez et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…This finding confirms the presence of a zoonotic parasite in an abundant invasive synanthropic bird widely distributed in Santiago (Briceño et al, 2022; Sandoval‐Rodríguez et al, 2021). In this study, four different and new sequences were identified, not previously available in GenBank.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These microclimate conditions in monk parakeet nests, combined with the colonial life and the reuse of chambers, can also promote a high parasite load that may negatively affect the breeding success of birds [47]. Moreover, in the invaded range, monk parakeets can acquire parasites from the recipient community and, in turn, can potentially introduce novel parasites and diseases into the recipient community [33,[48][49][50][51][52][53]. However, monk parakeets seem to be more resistant to infection by local parasites than native species [33], thus this transference of parasites could be strongly weighted towards native species.…”
Section: Discussionmentioning
confidence: 99%